An Introduction of a CIRGON Geoboard as a Manipulative for Teaching Geometry in K-12 Mathematics - Sibiya, Mandlenkosi Richard; Roux, Annalie; Kloppers, Magda (Studies in Learning and Teaching, 2025)
South African learners consistently underperform in mathematics, particularly in geometry, as shown by national and international assessments such as the Trends in Mathematics and Science Study (TIMSS). Euclidean geometry remains a major area of difficulty, with learners performing significantly worse than in other mathematical domains, signaling persistent challenges in teaching and learning. A key contributing factor is the mismatch between the reasoning required for Grade 12 geometry tasks (typically at Van Hiele level 3) and learners’ actual cognitive levels, which are often at Van Hiele level 1. This study adopts a practice-based research methodology to examine the effectiveness of the CIRGON Geoboard (CGG), a low-cost manipulative designed to support geometry instruction across the K–12 spectrum. Integrated into classroom practice and aligned with the Curriculum and Assessment Policy Statement (CAPS), the CGG promotes active, hands-on learning and scaffolds learners’ progression through the Van Hiele levels of geometric reasoning. Findings from classroom-based interventions indicate that the CGG enhances learner engagement and conceptual understanding, helping to bridge the gap between curriculum demands and learner capabilities. The study concludes that the CGG shows promise for addressing persistent challenges in geometry education and recommends further research into its long-term impact on learners’ geometric reasoning and problem-solving skills.